A challenge for Europe: meeting the national specifics in disaster and emergency management systems, towards attaining efficiency, resiliency and integration - Luciana Teodora Rotaru; Sorin Voicescu (CES Working Papers, 2017)
This paper highlights the advantages a more integrated European emergency care and disaster management system would bring in this very divided field of work through the lens of emergency physicians and contributors with a specific focus on the example Romania has to offer in matters of legislation, financing, dispatch centres, education and training of professionals, pre- and in-hospital care and European cooperation mechanisms. At the same time, we share the belief that this desiderate of attaining a certain degree of homogeneity inside the European Union is more likely to be reached by following slightly different paths, according to national specifics of the countries. To sustain this theory, we will bring various examples in our study of such events that already happened and together concurred to prove the above mentioned ideas. We do believe that the dream of a Europe without borders transforms unfortunately into a nightmare when it comes to disasters, which definitely know no borders. Our response to their threat should be standing together in unity and acting in solidarity.
Keywords: 330; European Union; emergency care; disaster management; resiliency; cooperation